2022
DOI: 10.3390/agronomy12020451
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Soil Redistribution Following Land Rehabilitation with an Apple Orchard in Hilly Regions of Central Iran

Abstract: This study was executed to explore soil redistribution and soil quality changes induced by land degradation and then rehabilitation by orchard plantation in different slope positions in a semi-arid region in central Iran. A total of 72 surface soil samples (0–30 cm) were collected from three land uses (natural rangelands, dryland farming, and apple orchards) in four slope positions (shoulder, backslope, footslope, and toeslope). The soil physicochemical properties and magnetic parameters were measured, and soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…In addition, our findings show that perennial agricultural crops such as oranges and mangoes generate the highest average gross margin (AGM) and are financially attractive options for local farmers. Although managing these fruit tree species may not be as effective in preventing soil erosion and controlling sedimentation as managing forests (Troeh et al, 1999;Liu et al, 2023), several studies have demonstrated that orchard management can reduce soil erosion by increasing the litter layer and improving soil conditions (Montanaro et al, 2017;Ayoubi et al, 2022). Ayoubi et al (2022) indicated that the improvement of soil conditions varies across spatial locations, such as footslope and toeslope, suggesting that growing fruit trees could provide a balanced approach between financial needs and soil erosion control, depending on the slope location.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, our findings show that perennial agricultural crops such as oranges and mangoes generate the highest average gross margin (AGM) and are financially attractive options for local farmers. Although managing these fruit tree species may not be as effective in preventing soil erosion and controlling sedimentation as managing forests (Troeh et al, 1999;Liu et al, 2023), several studies have demonstrated that orchard management can reduce soil erosion by increasing the litter layer and improving soil conditions (Montanaro et al, 2017;Ayoubi et al, 2022). Ayoubi et al (2022) indicated that the improvement of soil conditions varies across spatial locations, such as footslope and toeslope, suggesting that growing fruit trees could provide a balanced approach between financial needs and soil erosion control, depending on the slope location.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies on the effects of orchard management on soil quality are limited (Ayoubi et al, 2022). Future research in this region should further investigate the effects of fruit orchards on soil quality, soil erosion, and sedimentation.…”
Section: Discussionmentioning
confidence: 99%
“…Vegetation in the landscape fulfills a number of ecosystem functions, such as reducing soil erosion, improving soil health, phytomedical functions, food sources for animals, and aesthetic and cultural functions [71][72][73][74]. Higher species diversity of vegetation is a prerequisite for the successful fulfillment of these functions [75,76].…”
Section: Discussionmentioning
confidence: 99%
“…The properties of soil as the conventional growing media become a significant part of being analyzed since it is related to the nutritional supply for the plants. Studies on soil properties have been widely conducted on various types of planting land (Ayoubi et al, 2022;Lambert et al, 2008;Butnor et al, 2003;Kai & Kubo, 2020). For example, the study on clay mineral and its correlation with potassium formation in the land planted with paddy and other than paddy (Raheb & Heidari, 2011).…”
Section: Introductionmentioning
confidence: 99%